Identification of clusters: An actor-based approach - Thomas Brenner (Philipps-University Marburg, Department of Geography, 2017)
This paper provides two things. First, it gives an overview on the existing top-down methods for the identification of clusters (Section II). Second, it presents a new method that has been recently introduced by Scholl and Brenner (2016) in a basic version. However, the existing version of this approach is limited and does not take full advantage of its potential. The approach is further developed here and its characteristics and the procedure of its use are presented and discussed in detail (Section III).
Keywords: C43; R12; L60; 330; cluster; cluster identification; spatial methods